"Raw Intelligence Does Not Help You": Exploring Teachers' Conceptualizations of Success at One "No-Excuses" Charter School. (September 2021) - Marsh, L. Trenton S.
This paper explores the ways in which success in school is constructed by a majority White teaching staff during day-to-day classroom practices and schoolwide policies, such as the disciplinary systems at a "no-excuses" charter school in one of the largest urban districts in the U.S. Stakeholders were assessed by interviews and observations during a year-long situated ethnography with an analysis of teachers' dispositions and actions. As "no-excuses" public charters are proliferated across the country due to purported students' success, it is important to understand how success in school is conceptualized and measured by teachers.